PENGARUH BEBERAPA PERLAKUAN TERHADAP PENGURANGAN KADAR FORMALIN PADA IKAN YANG DITENTUKAN SECARA SPEKTROFOTOMETRI - Yusuf, Yulizar; Zuki, Zamzibar; Amanda, Ruci Riski (Jurnal Riset Kimia, 2015)
The case of how handling the fresh fish which used the dangerous chemical material (formaldehyde) is still found in society, so that is why it is necesarry to find the safety way to handle the fresh fish in. It has been held the research about the influence of on the effect of some treatment in reduction the formaldehyde level on fish determined by spectrophotometry UV-Visible at wavelength 412 nm and 40Â°C. In the preliminary research the fish is soaked in formaldehyde liquid (100 mg/mL) for 24 hours, then washed, soaked and boiled. Then, the filtrate is reacted with Nash reagent. The yellow color which has formed was measured at Î» 412 nm. The result shows there is the reduction of formaldehyde level in the sample about 43.9 % after washing, 33.3 % after soaking, 53.8 % after boiling. After that, the fish that was spread in the market which suspected containing the formaldehyde then washed, soaked and boiled. The result shows there is the reduction of formalin level in sample 1 about 22,7 % after washing, 17.0% after soaking, and 96.1 % after boiling. While in sample 2, 41.8 % after washing, 56.2 % after soaking, and 95.4 % after boiling.